FAKTOR -FAKTOR YANG MEMPENGARUHI MINAT INVESTOR DALAM BERINVESTASI SUKUK - Zaeni, Dewi Astuti (Fakultas Ekonomi dan Bisnis Islam, 2020)
Abstract Sukuk is a sharia investment which now has a lot of demand. It is no doubt in Indonesia that sukuk are now beginning to increase. Based on the data compiled, Retail State Sukuk investors are still mostly from DKI Jakarta, Java and Western Indonesia. The increase is certainly based on several factors. This study aims to determine what factors influence sukuk investment interest. The method used in this study is to use data collection methods by taking data from several previous studies, interviewing investors and studying literature that supports problem solving. The results of data processing show that the factors that influence the interest of investors to increase sukuk are one of them is the low risk that will be borne by investors. Keywords: Sukuk investment; Investment Risk; Interest Factor